PEMIKIRAN EKONOMI ISLAM DARI AL-GHAZALI - Furqonul Haq (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2023)
Islamic economists from Indonesia, in deepening their knowledge of Islamic economics, must have been more or less inspired by the Islamic economists of the past. This can be seen from the inclusion of the theories of earlier Islamic economists in their works. There were many Islamic economists in the past, one of whom was Al-Ghazali. This study aims to analyze the Islamic economic thought of Al-Ghazali. The research method was carried out by means of a literature study. The results of the study show that Al-Ghazali's Islamic economic thought is generally contained in nine aspects, namely: market evolution, money evolution and barter issues, usury and money exchange, money hoarding and counterfeiting, production activities, public sector regulation, as well as the role of the state and financial public. Al-Ghazali greatly contributed to the treasures of Islamic economics